Synthesis of tetrahydro-5-azaindoles and 5-azaindoles using pictet-spengler reaction-appreciable difference in products using different acid catalysts - Shumaila, Abdullah M. A.; Puranik, Vedavati G.; Kusurkar, Radhika S. (Tetrahedron, 2011)
Pictet-Spengler condensation of 2-(aryl)-2-(1H-pyrrol-2-yl)ethanamines using conventional acid catalysts like TMSCl or TFA resulted in the formation of substituted 5-azaindoles involving a tandem one pot four steps reaction sequence. By contrast use of glacial acetic acid furnished the targeted tetrahydro-5-azaindoles in diastereoselective manner. These were readily dehydrogenated to 5-azaindoles. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: 2-(Aryl)-2-(1H-pyrrol-2-yl)ethanamines; 4; 7-Disubstituted-5-azaindoles; 7-Disubstituted-tetrahydro-5-azaindoles; Diastereoselective Pictet-Spengler reaction